Emulsifiers and thickeners on extrusion-cooked instant rice product - Wang, Jin Peng (Springer-Verlag, 2011)
Extrusion-cooked instant rice was prepared by optimizing the formulation with emulsifiers, glycerol monostearate (GMS), soybean lecithin (LC), and sodiumstearoyl lactylate (SSL), and thickeners, gum Arabic (GA), sodium alginate (SA), and sticky rice (SR). The emulsifiers addition caused increase of degree of gelatinization (DG), and decrease of water soluble carbohydrate (WSC), α-amylase sensitivity, water soluble index (WAI) and adhesive for extrudates, while the thickeners addition increased extrudates DG, bulk density (BD), WSC, α-amylase sensitivity, WAI, hydration rate (HR) and adhesiveness. Based on the data generated by a single additive at various levels, optimum formulation was obtained employing orthogonal matrix system with combination of the selected additives for extrusion cooking. Extrudates were evaluated for optimum hydration time followed by drying to prepare the finished product. Texture profile analysis and sensory evaluation indicate that quality of the finished product is equivalent to that of the round shaped rice and superior to a commercial instant rice product. This study also demonstrates possibility of value-added and versatile instant rice product development using broken rice.